Molecular interaction of stress granules with Tau and autophagy in Alzheimer's disease. (July 2022) - Yu, Qin-Yuan; Ye, Ling-Qi; Li, Hong-Lei
Abstract: Stress Granules (SGs) are RNA granules composed of untranslated mRNA and associated proteins, which are related to the cytoplasmic metabolism of mRNA in response to cellular stress and certain drug stimuli. Physiological SGs are dynamic structures that protect cells from the effects of stress, and continuous stress ripens the SGs into more stable complexes. Numerous studies have found that dysregulation of RNA metabolism in stress response led to misfolded protein aggregation in the pathophysiology of neurodegenerative diseases. For example, in neurodegenerative diseases such as amyotrophic lateral sclerosis (ALS), frontotemporal dementia (FTD), Alzheimer's disease (AD), and Parkinson's disease (PD), SGs aggregation is mainly due to up-regulation of SGs formation and down-regulation of SGs clearance. Recent studies have revealed the role of SGs in the pathogenesis and pathology of AD, especially the interaction of SGs and RNA-binding proteins with Tau and autophagy. Aggregation of SGs and increased RNA-binding proteins, especially TIA1, can facilitate Tau misfolding and propagation, and vice versa. Autophagy dysfunction disrupts the normal pathway of SGs clearance. In this review, we summarized the regulation of SGs and their relationship with Tau protein and autophagy, as well as the pathological mechanisms of AD such as RNA splicing, microglial cell proliferation and phagocytosis. Highlights: The abnormal regulation of stress granule formation and clearance promotes the pathological process of AD. The aggregation of stress granules and RNA-binding proteins facilitate the misfolding and propagation of Tau protein. Autophagy-lysosome system dysfunction in Alzheimer's Disease inhibits SG removal.